Prevalence and predictors for spontaneous bacterial peritonitis in cirrhotic patients with ascites admitted at medical block in korle-bu teaching hospital, Ghana - Nkrumah, K.N.; Nkrumah, A. (Pan African Medical Journal (PAMJ), 2019)
Introduction: spontaneous bacterial peritonitis (SBP) is one of the most common and life-threatening complications of patients with cirrhotic ascites. Recognition and prompt treatment of this condition is essential to prevent serious morbidity and mortality. This study aimed to determine the prevalence of SBP among in-patients with cirrhotic ascites attending our facility and to determine the clinical and laboratory parameters associated with SBP. Methods: a cross-sectional study was conducted involving one hundred and three (103) patients admitted at medical block in the Korle-Bu Teaching Hospital (KBTH) with cirrhotic ascites from 25th March, 2016 to 25th November, 2016. Demographic and clinical data were collected using a standardized questionnaire. Ascitic fluid culture and cell count were conducted. Positive ascitic fluid culture and/or ascitic polymorphonuclear leukocyte ≥ 250cells/mm3 were diagnostic for SBP. Results: of the 103 patients with cirrhotic ascites, the mean age was 43.5 ± 12.2 years. There were fifty eight (58) male patients. The prevalence of SBP was 25.24% (26/103). Majority, 5 (55.6%) of the bacteria isolated from ascitic fluid with SBP was Escherichia coli. Severe ascites and high INR were found to be independent predictors of SBP. Conclusion: SBP is common among patients with cirrhotic ascites admitted at KBTH. Severe ascites and high INR were highly suggestive of SBP. Diagnostic paracentesis should be done immediately on admission to confirm the diagnosis irrespective of the clinical characteristics as part of baseline investigation.
Research Article
Keywords: Liver cirrhosis; spontaneous bacterial peritonitis; ascites; Ghana